2000
DOI: 10.1046/j.1365-2125.2000.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Graft material and results of platelet inhibitor trials in peripheral arterial reconstructions: reappraisal of results from a meta‐analysis

Abstract: Aims To investigate the characteristics of published trials in order to establish the origin of the differing results obtained in trials of platelet inhibitors after peripheral bypass procedures. Methods Analysis of the information from 11 randomised, controlled trials of platelet inhibitors after peripheral bypass procedures published up until 1999 and involving 2302 patients undergoing peripheral bypass operations, 1250 of whom were treated with platelet inhibitors. Results There is a signi®cant treatment be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…32,33 A third metaanalysis concluded that the improvement in graft patency seen with platelet inhibitors was attributed to an effect on synthetic grafts, and that no benefit was appreciated in vein grafts. 34 The Dutch Bypass Oral Anticoagulants or Aspirin Study Group recently concluded, on the basis of a prospective randomized trial, that aspirin was of benefit in the prevention of prosthetic but not autogenous graft occlusion. 35 The association of tibial distal anastomotic sites and an increased incidence of thrombosis is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 A third metaanalysis concluded that the improvement in graft patency seen with platelet inhibitors was attributed to an effect on synthetic grafts, and that no benefit was appreciated in vein grafts. 34 The Dutch Bypass Oral Anticoagulants or Aspirin Study Group recently concluded, on the basis of a prospective randomized trial, that aspirin was of benefit in the prevention of prosthetic but not autogenous graft occlusion. 35 The association of tibial distal anastomotic sites and an increased incidence of thrombosis is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of antiplatelet therapy on prosthetic graft patency has been supported by a meta-analysis of all trials since 1999. 163 The Dutch BOA study (see previously) compared antiplatelet therapy with aspirin to VKA alone. 135 In the subgroup of 1,100 patients with prosthetic grafts, VKA was inferior to aspirin (hazard ratio 1.32, 95% CI 0.81-2.15).…”
Section: Antiplatelet Agentsmentioning
confidence: 99%
“…The role of anticoagulation and platelet inhibitors for different bypass materials after infrainguinal surgery is well documented by several prospective randomised trials and meta-analyses. [16][17][18][19][20][21] In preventing prosthetic infra-inguinal bypass graft occlusions, low dose ASA is superior to vitamin K antagonists. Oral anticoagulation, on the other hand, does improve long-term patency rates for infrainguinal venous bypass grafts compared to ASA.…”
Section: Discussionmentioning
confidence: 99%